Sensory assessments and consumers’ willingness to pay for Karoo lamb versus Karoo mutton using an experimental auction approach - Troost, Carina (Stellenbosch : Stellenbosch University, 2019)
Thesis (MCom)--Stellenbosch University, 2019.